Transpiration in Quercus suber trees under shallow water table conditions: the role of soil and groundwater - Pinto, Clara A.; Nadezhdina, Nadezhda; David, Jorge S; Kurz-Besson, Cathy; Caldeira, Maria C; Henriques, Manuel O; Monteiro, Fernando G; Pereira, João S; David, Teresa S (Hydrological Processes, 2013)
Water is one of the major environmental factors limiting plant growth and survival in the Mediterranean region. Quercus suber L. woodlands occupy vast areas in the Iberian Peninsula, frequently under shallow water table conditions. The relative magnitude of soil and groundwater uptake to supply transpiration is not easy to evaluate under these circumstances. We recently developed a conceptual framework for the functioning of the root system in Q. suber that simulates well tree transpiration, based on two types of root behaviour: shallow connected and deep connected. Although this significantly improved knowledge on the functional traits of Mediterranean Q. suber, the approach has the limitation of requiring root sap flow data, which are seldom available. In this work, we present alternative methodologies to assess if trees are connected to groundwater and to estimate the soil and groundwater contributions to tree transpiration. We provide evidence on the tree unrestricted access to groundwater solely based on meteorological, stem sap flow and leaf water potential data. Using a soil mass balance approach, we estimated the yearly soil and groundwater contributions to tree transpiration: 69.7% and 30.3%, respectively. Groundwater uptake became dominant in the dry summer: 73.2% of tree transpiration. Results reproduce extremely well those derived from root modelling. Because of its simplicity both in formulation and data requirements, our approach is potentially liable to be adapted to other groundwater- dependent Mediterranean oak sites, where interactions between land use and water resources may be relevant.
Keywords: Cork oak; ecohydrology; sap flow radial profile; tree water sources; tree water use; water balance

Soil water content at the catchment level and plant water status relationships in a Mediterranean Quercus ilex forest - Bellot, J; Ortiz de Urbina, J M (Journal of Hydrology, 2008)
This paper presents an analysis of the forest hydrology and plant water status interaction, focusing on the relationship between the hydrological water balance at the catchment level and the predawn leaf water potential of the species Quercus ilex (holm oak). The catchment water balance approach was applied to a Mediterranean watershed forested with holm oak to evaluate the daily soil water reserve at the catchment level. After this, evapotranspiration and soil water content were combined to estimate the potential soil water reserve and evaluate plant water status at the catchment level. A close relationship was detected between leaf water potential and the soil water reserve, and was ﬁtted to a negative exponential curve to estimate predawn leaf water potential from a hydrological database. The proposed equation can help to predict the frequency, intensity, and length of droughts potentially capable of causing structural damage to the forest, from the hydrological time series records.
Keywords: Catchments; Plant water status; Predawn water potential; Quercus ilex; soil water; water balance

Soil water content at the catchment level and plant water status relationships in a Mediterranean Quercus ilex forest - Bellot, J.; Ortiz de Urbina, J. M. (Journal of Hydrology, 2008)
This paper presents an analysis of the forest hydrology and plant water status interaction, focusing on the relationship between the hydrological water balance at the catchment level and the predawn leaf water potential of the species Quercus ilex (holm oak). The catchment water balance approach was applied to a Mediterranean watershed forested with holm oak to evaluate the daily soil water reserve at the catchment level. After this, evapotranspiration and soil water content were combined to estimate the potential soil water reserve and evaluate plant water status at the catchment level. A close relationship was detected between leaf water potential and the soil water reserve, and was ﬁtted to a negative exponential curve to estimate predawn leaf water potential from a hydrological database. The proposed equation can help to predict the frequency, intensity, and length of droughts potentially capable of causing structural damage to the forest, from the hydrological time series records.
Keywords: Catchments; Plant water status; Predawn water potential; Quercus ilex; soil water; water balance

Effects of environmental stress on forest crown condition in Europe. Part II: Estimation of stress induced by meteorology and air pollutants - Leeuwen, E. P. Van; Hendriks, KCMA (Water, Air, & Soil Pollution, 2000)
In order to assess the relationship between environmental stress and crown condition of forest trees monitored since 1986 in Europe, estimates of stress factors, including temperature stress, drought stress and air pollution stress, were derived with the best data, methods and models currently available. This paper presents information on the methods used to derive such stress factors, and on the overall ranges, the temporal trends, the spatial distribution and the reliability of the calculated stress factors. The temperature stress indices did not show much temporal variation between 1985 to 1995. As expected spatial patterns were north-south orientated, going from colder northern regions to warmer southern regions. The calculated relative transpiration showed a more complex pattern, coinciding to a large extend with patterns of rainfall and temperature. Potential acid deposition decreased between 1986 and 1992, but remained fairly constant after 1992. The strong decrease was mainly the result of the decrease in SOx deposition, and to a small decrease in NOy deposition. Highest levels of the S and N deposition were calculated in Central and Western Europe. Base cation deposition was largest in coastal areas and in southern Europe. This is mainly due to soil dust, Sahara dust and sea salt. Base cation deposition can compensate almost entirely for the potential inputs in the south of Europe, whereas in central Europe it equalled about 25% of the potential acid input. A comparison between site speciﬁc modelled deposition and deposition derived from throughfall data showed that the total acid deposition is usually overestimated by the model, whereas the total nitrogen deposition is underestimated, especially at plots with high nitrogen loads. There is, however, a signiﬁcant correlation between measured and modelled data for all S and N deposition, thus allowing their use in a statistical analyses.
Keywords: acidity; air pollution; ammonia; atmospheric deposition; Base cations; deposition model; Drought; nitrogen oxides; Ozone; sulphur; temperature stress; water balance

The dehesa system of southern Spain and Portugal as a natural ecosystem mimic - Joffre, R; Rambal, S; Ratte, J P (Agroforestry Systems, 1999)
The dehesas of the southwestern Iberian Peninsula are ‘man-made’ ecosystems characterised by a savannah-like physiognomy. The trees are viewed as an integrated part of the system, and as a result are planted, managed, and regularly pruned. Palynological and historical evidence of the manipulation of initial ecosystems by man to obtain a savannah-like ecosystem is presented. The ecological functions of the tree are detailed using results obtained at two complementary scales. At the local scale, strong soil structural differences and functional differences in water budget and patterns of water use are observed under and outside the tree canopy. Using the concept of ecosystem mimicry, the two coexistent components of dehesas can be compared to two distant stages of a secondary succession characterised by very different behaviours. At the regional scale, evidence of relationships between tree density and mean annual precipitation over more than 5000 km2 suggests that the structure of these man-made agroecosystems have adjusted over the long-term and correspond to an optimal functional equilibrium based on the hydrological equilibrium hypothesis. Finally, the future of dehesas in the face of contemporary exogenous threats of economic and global environmental origin is discussed. 1. Introduction
Keywords: hydrological equilibrium; Mediterranean climate; optimality; Quercus ilex; Quercus suber; water balance

Hydrological influences on the resilience of Quercus spp. dominated geoecosystems in central Spain - Bergkamp, Ger (Geomorphology, 1998)
Differences in vegetation cover within a landscape having a similar land use history, can be used to identify differences in recovery following disturbance according to landscape position. The objective of this study was to determine the resilience of oak-dominated communities at different landscape positions in a research area in central Spain as indicated by the relative recovery of Quercus ilex and Q. coccifera, and to relate this to the most important hydrological processes and properties at the slope sections scale. The results indicate that the geoecosystems on slope sections on north-facing slopes are more resilient than those on south-facing slopes. On the more degraded shrubland sites, the higher values of vegetation cover on the lower slope sections indicate the systems on these slope sections to be more resilient than those on the slope sections located higher up the slope. The hydrological factors that could possibly explain differences in vegetation type and cover were found to be distance to water resources at greater depths and incoming radiation controlling evapotranspiration. A conceptual model is presented that links the resilience of these systems to the hydrological conditions. On the basis of the presented model, it is postulated that recovery of the system is determined partly by access to deep water resources. It is suggested that differences in or degree of access to such water resources may cause these comparably looking systems to react differently to degradation and recovery
Keywords: Mediterranean; Quercus; resilience; Shrubland; water balance

Hydrological influences on the resilience of Quercus spp. dominated geoecosystems in central Spain - Bergkamp, Ger (Geomorphology, 1998)
Differences in vegetation cover within a landscape having a similar land use history, can be used to identify differences in recovery following disturbance according to landscape position. The objective of this study was to determine the resilience of oak-dominated communities at different landscape positions in a research area in central Spain as indicated by the relative recovery of Quercus ilex and Q. coccifera, and to relate this to the most important hydrological processes and properties at the slope sections scale. The results indicate that the geoecosystems on slope sections on north-facing slopes are more resilient than those on south-facing slopes. On the more degraded shrubland sites, the higher values of vegetation cover on the lower slope sections indicate the systems on these slope sections to be more resilient than those on the slope sections located higher up the slope. The hydrological factors that could possibly explain differences in vegetation type and cover were found to be distance to water resources at greater depths and incoming radiation controlling evapotranspiration. A conceptual model is presented that links the resilience of these systems to the hydrological conditions. On the basis of the presented model, it is postulated that recovery of the system is determined partly by access to deep water resources. It is suggested that differences in or degree of access to such water resources may cause these comparably looking systems to react differently to degradation and recovery
Keywords: Mediterranean; Quercus; resilience; Shrubland; water balance

HOW TREE COVER INFLUENCES THE WATER-BALANCE OF MEDITERRANEAN RANGELANDS - Joffre, R; Rambal, S (ECOLOGY, 1993)
Dehesa ecosystems of the southwestern Iberian Peninsula are characterized as a savanna-like rangeland dominated by scattered mediterranean evergreen oak trees. We investigated whether isolated trees modify the water balance of this ecosystem and if so, what implications this finding might have on models that assume homogeneity of soil water resources. The water balance of the two ecological components of the dehesas-(1) the tree-grass component, and (2) the open areas between the tree canopies with unshaded grass vegetation-was studied for three consecutive years in three locations in the Sierra Norte de Sevilla region of Andalusia in southern Spain. In this region, annual rainfall was generally between 600 and 800 mm, and the summer drought lasted almost-equal-to 130 d. Soil water storage was measured with a neutron moisture gauge outside and under the tree canopy. Deep drainage between two consecutive census dates was calculated using field-measured drainage characteristics. Evapotranspiration (Ea) and surface runoff were computed from the water balance equation assuming that Ea is limited by Penman potential evapotranspiration. Monthly Ea by annual species in open areas was poorly correlated with rainfall levels in the autumn and was limited during the spring by availability of water in the top 40 cm of soil. During summer, monthly Ea by trees ranged from 30 to 50 mm. Mean annual Ea was 400 mm outside and 590 mm under the tree cover. In open areas, water yield (WY), defined as the sum of deep drainage and surface runoff, ranged from 65 to 100% of total Ea, whereas under the tree canopy WY was only 20 to 40% of the Ea. Under the tree canopy, when annual precipitation was < 570 mm, WY was negligible and all precipitation was lost by evapotranspiration. Outside the tree canopy, WY occurred as soon as annual precipitation exceeded 250 mm. Models of competition between trees and grass generally assume a spatial homogeneity of soil hydrodynamic properties. Our results, however, show that both soil water storage and evapotranspiration are greater for the tree-grass component. Consequently, these models must account for this spatial variability in water resources according to species.
Keywords: DEEP DRAINAGE; Dehesa; Evapotranspiration; Grasses; hydrological equilibrium; MEDITERRANEAN OAK WOODLANDS; Quercus ilex; Quercus-suber; surface runoff; Trees; water balance

Estudos de hidrologia em povoamentos de Quercus suber e caracterizaçao mesológica do ecossistema - Almeida, A. P. (Scientia gerundensis, 1992)
The main objective of the project is to assess the effect of different types of soil management under cork-oak tree stands on water use and cork productivity. The study utilized a 5.5 ha watershed near the town of Mora, center of Portugal. The watershed contained scattered cork- oak with natural pasture, which is probably the most representative formof landuse in the region. de 1990, que va mostrar la The project used the basic water balance equation, being evaluated incident rainfall, runoff, evapotranspiration and changes in soil water storage. Measurements of the tree stands and canopies were included for the characterization of throughfall and stemflow. Interception was estimated to evaluate its effects onrainfallredistribution and onthe dynarnics of evapotranspiration. Collection of data for the intensive hydrologic study begun in October 1, 1988. During 1989, surface runoff was 10.8 percent of annual rainfall. For the same period, canopy interception by the Quercus suber stand was 15.4 percent and throughfall accounted for 84.6 percent of annual rainfall, as stemfiow was considered negligible. Statistical analysis of data related to the period January, 1990 to May, 1990 is now being undertaken. Itis apparent, however, from the study, that the data sets should be extended through further research to confirm the tentative hydrological trends of the first period.
Keywords: cork-oak; land use; pasture; productivity; water balance